The Edinburgh companion to First World War periodicals - Demoor, Marysa; Dijck, Cedric van; Van Puymbroeck, Birgit (Edinburgh : Edinburgh University Press, 2023)
The first reference book on First World War newspapers and magazines from the home front to the front lines.
Frontmatter -- Contents -- Figures and Tables -- Acknowledgements -- Introduction -- Part I: Critical Approaches -- 1 Materiality -- 2 Networks -- 3 (Digital) Archives -- 4 Affect and Emotion -- 5 Memory -- 6 Popular Culture -- Part II: Contributors -- 7 Authors -- 8 Artists -- 9 Editors -- 10 Journalists -- 11 War Correspondents -- 12 Photographers -- Part III: Events -- 13 Beginnings -- 14 Battles -- 15 Alliances -- 16 The Armenian Genocide -- 17 Revolutions -- 18 The Influenza Pandemic -- Part IV: Types of Periodicals -- 19 Trench Journals -- 20 Prisoner-of-War Camp Journals -- 21 Hospital Journals -- 22 Pacifist Journals -- 23 Women's Suffrage and Labour Journals -- 24 Avant-garde Journals -- Part V: Global Perspectives -- 25 German Colonial Africa -- 26 India -- 27 Australia and New Zealand -- 28 China -- 29 Canada -- 30 The Ottoman Empire -- Notes on Contributors -- Index
Description based upon online resource; title from PDF title page (viewed Jan 16th, 2023).
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: World War, 1914-1918 -- Periodicals; World War, 1914-1918 -- Press coverage; Guerre mondiale, 1914-1918 -- Périodiques.; Guerre mondiale, 1914-1918 -- Couverture de presse; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh; Press coverage; Literary reference works; Encyclopaedias & reference works; General & world history; European history; Warfare and Defence; 1914-1918; Periodicals